Analisis Dana Perlindungan Pemodal (Securities Investor Protection Fund) Sebagai Sarana Perlindungan Hukum Investor Di Pasar Modal - Ryan Ozora Hendrawan; Lastuti Abubakar; Nun Harrieti (Universitas Medan Area, 2023)
This research aims to look at the Financial Services Authority (OJK) establishing an Investor Protection Fund (DPP) to protect investors in the capital market. This study discusses the scope of DPP protection and the effectiveness of DPP implementation in the capital market. The problem is focused on the DPP having a fairly narrow scope of protection, namely protection only for the loss of investor assets caused by the custodian, and only for SIPF members. The effectiveness of DPP implementation can be seen from two sides, namely as a compensation fund and as an investment fund. To approach the problem, references from the Law of the Agreement are used. The data were collected through literature and field studies, document study data collection tools, and interviews and were analyzed descriptively and qualitatively.This study concludes that the implementation of DPP can be divided into two types, namely DPP with its function as a compensation fund and DPP with its function as an investment fund, the implementation of DPP as an investment fund has been effective, as can be seen from its rapid development